Assessing the impacts of aminoethoxyvinylglycine and 1-methylcyclopropene on fruit drop, cracking, quality, and related transcript accumulation in ‘Ambrosia’ and ‘Fuji’ apples during on-the-tree ripening - Johnson, Emily; Farcuh, Macarena (Frontiers in Plant Science, 2025)
Fruit drop, cracking, and advanced ripening prior to fruit harvest can promote significant losses in important apple cultivars such as ‘Ambrosia’ and ‘Fuji’ grown in the mid-Atlantic. These losses result from environmental factors, delays in harvest due to the lack of red skin color development, and cultivar-specific characteristics, among others. Aminoethoxyvinylglycine (AVG) and 1-methylcyclopropene (1-MCP) are ethylene-inhibiting plant growth regulators (PGRs) that can alter preharvest fruit drop, cracking, maturity, and quality by impeding ethylene biosynthesis and perception, respectively. However, there is a knowledge gap on understanding the impacts of specific timings and dosages of such PGR treatments on ‘Ambrosia’ and ‘Fuji’ under mid-Atlantic environmental conditions. The objective of this work was to characterize and compare the impacts of specific rates of preharvest ethylene-inhibiting PGRs on fruit drop and cracking, ethylene production, physicochemical properties, skin color, and associated gene expression in ‘Ambrosia’ and ‘Fuji’ apples during on-the-tree ripening. Multivariate statistical methods for identifying meaningful correlations among the measured variables were applied. Our results show that both full-rate AVG (130 mg a.i. L−1) and 1-MCP (150 mg a.i. L−1) significantly reduced preharvest fruit cracking compared with control fruits in ‘Ambrosia’, but not in ‘Fuji’. Furthermore, among all treatments, full-rate AVG (130 mg a.i. L−1) treatment displayed the lowest ethylene production and gene expression of ethylene- related genes. 1-MCP (150 mg a.i. L−1) and half-rate AVG (65 mg a.i. L−1) treatments presented a reduction in the ethylene production and gene expression of ethylene-related genes when compared to control fruits. Regarding color, apple skin blush and anthocyanin-related gene expression were the lowest in full-rate AVG (130 mg a.i. L−1)-treated fruits, explaining why these fruits met the 50% red blush coverage 1 week later than all other treatments in both cultivars. Correlations amongst the assessed features were also identified. These results suggest a cultivar-specific effectiveness under mid-Atlantic conditions and specifies a framework for the use of ethylene-inhibiting PGRs under mid-Atlantic environmental conditions.